Genetic Barriers to Historical Gene Flow between Cryptic Species of Alpine Bumblebees Revealed by Comparative Population Genomics. (6th April 2021) - Christmas, Matthew J; Jones, Julia C; Olsson, Anna; Wallerman, Ola; Bunikis, Ignas; Kierczak, Marcin; Peona, Valentina; Whitley, Kaitlyn M; Larva, Tuuli; Suh, Alexander; Miller-Struttmann, Nicole E; Geib, Jennifer C; et al.
Abstract: Evidence is accumulating that gene flow commonly occurs between recently diverged species, despite the existence of barriers to gene flow in their genomes. However, we still know little about what regions of the genome become barriers to gene flow and how such barriers form. Here, we compare genetic differentiation across the genomes of bumblebee species living in sympatry and allopatry to reveal the potential impact of gene flow during species divergence and uncover genetic barrier loci. We first compared the genomes of the alpine bumblebee Bombus sylvicola and a previously unidentified sister species living in sympatry in the Rocky Mountains, revealing prominent islands of elevated genetic divergence in the genome that colocalize with centromeres and regions of low recombination. This same pattern is observed between the genomes of another pair of closely related species living in allopatry ( B. bifarius and B. vancouverensis ). Strikingly however, the genomic islands exhibit significantly elevated absolute divergence ( d XY ) in the sympatric, but not the allopatric, comparison indicating that they contain loci that have acted as barriers to historical gene flow in sympatry. Our results suggest that intrinsic barriers to gene flow between species may often accumulate in regions of low recombination and near centromeres through processes such as genetic hitchhiking, and that divergence in these regions is accentuated in the presence of gene flow.